Effect of Rainfall Pattern on Sediment Yield and Runoff in Different Textured Soils - Abdul-rahman Perdawood Haydar; Kamyar Mutalib Mohammed; Dawod Rasooli Keya (Polytechnic Journal)
Evaluating the impacts of rainfall intensities on bulk density, runoff rate, and sediment yield is critical in soil characterization and sediment transport. The primary objective of this research is to use multiple linear regression analysis to establish several models correlating rainfall intensity, silt content, and clay content with bulk density, sediment yield, and runoff rate. Several soil samples from different locations in Erbil, Iraq, were collected. Soil samples were placed in a rainfall simulator and brought back to in-situ conditions. The parameters of the suggested models for predicting bulk density, runoff rate, and sediment yield were estimated using linear and non-linear least squares approaches in Microsoft Excel, and the results of the suggested models were validated by several model performance indicators. The results showed that the 3-parameter bulk density and runoff rate models were the best-performing models with coefficients of determination (R2 ) of 0.923 and 0.931 respectively. However, the model relating rainfall intensity and clay content with sediment yield showed the best performance with an adjusted R2 of 0.675 and the lowest values for mean absolute error and root mean square error (93.976 and 72.104, respectively). The results also showed that coefficients of variation were less than 15 % for all predicted and measured bulk density, sediment yield, and runoff rate models. In conclusion, the correlation of rainfall intensity with bulk density and runoff rate is significant. Integrating rainfall intensity, silt, and clay led to the largest increase in the coefficient of determination in bulk density and runoff rate models while the largest increase was noticed when relating rainfall intensity and clay content with sediment yield.